2016
DOI: 10.1055/s-0036-1582317
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Meldonium (Mildronate) from Blood, Dried Blood Spots (DBS), and Urine Suggest Drug Incorporation into Erythrocytes

Abstract: Initially developed in the late 1970s for veterinary applications due to proposed growth-promoting effects in animals [5], meldonium has become an approved drug in selected Eastern European countries and is the subject of ongoing clinical trials focusing the compound's anti-ischemic and cardioprotective properties [2,3,12,15] as well as potential applications regarding diabetes, neurodegenerative disorders, and bronchopulmonary diseases. In the context of athletic performance, beneficial effects on the individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 17 publications
0
39
0
Order By: Relevance
“…In their recent ‘Notice-Meldonium’,9 WADA put emphasis on this issue by providing the stakeholders with new information on preliminary results obtained from single and multiple drug applications. First light on the discussion on meldonium's elimination brought a recent pilot study by Tretzel et al 60. Preliminary data could demonstrate that there exists a second, very slow elimination phase of meldonium with urinary concentrations of 80 ng/mL 16 days and between 10 and 200 ng/mL for up to 49 days postadministration after a single dose of 500 mg. Urinary meldonium concentration profiles revealed values between 1 and 9 μg/mL after multiple applications (3×500 mg/day for 6 days) until day 33.…”
Section: Introductionmentioning
confidence: 99%
“…In their recent ‘Notice-Meldonium’,9 WADA put emphasis on this issue by providing the stakeholders with new information on preliminary results obtained from single and multiple drug applications. First light on the discussion on meldonium's elimination brought a recent pilot study by Tretzel et al 60. Preliminary data could demonstrate that there exists a second, very slow elimination phase of meldonium with urinary concentrations of 80 ng/mL 16 days and between 10 and 200 ng/mL for up to 49 days postadministration after a single dose of 500 mg. Urinary meldonium concentration profiles revealed values between 1 and 9 μg/mL after multiple applications (3×500 mg/day for 6 days) until day 33.…”
Section: Introductionmentioning
confidence: 99%
“…A study of the pharmacokinetics of single‐use (500 mg) and multiple‐use (500 mg three times per day for six days) of meldonium showed the presence of the second, longer, elimination phase of the drug, with determined concentrations in urine . A single dose of meldonium for 16 days yielded a mean urinary concentration of 80 μg/mL, and at 49 days produced individual concentrations ranging from 10 to 200 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…18 A study of the pharmacokinetics of single-use (500 mg) and multiple-use (500 mg three times per day for six days) of meldonium showed the presence of the second, longer, elimination phase of the drug, with determined concentrations in urine. 19 The effectiveness of this transfer depends on medium pH and pKa values of the drug's corresponding ionogenic group. However, at high-density substrate, which was simulated during the present study, this process may also reach the saturation limit.…”
Section: The Impact Of L-carnitine On the Pharmacokinetics Of Meldomentioning
confidence: 99%
“…The tissue accumulation may be a result of meldonium's affinity for the organic cation transporter‐2 which leads to reabsorption in the renal tubules as well as uptake in various tissues, including the heart and skeletal muscle, containing this transporter . A recent study in humans demonstrated that meldonium incorporates into red blood cells and the investigators hypothesized that the slow release of the drug from erythrocytes, which have a lifespan of 70–140 days, could explain the long elimination half‐life and prolonged detection time . The lifespan of erythrocytes in horses is approximately 145 days.…”
Section: Discussionmentioning
confidence: 99%